Using information technology : a practical introduction to computers & communications - Williams, Brian K., 1938-; Sawyer, Stacey C. (New York : McGraw-Hill, 2015)
The tumultuous changes in the landscape of information technology over the last two years have led us to make extensive modifications in this edition of USING INFORMATION TECHNOLOGY - to do not just a revision but a remaking and reimagining of this computer concepts book." -Brian K. Williams & Stacey C. Sawyer A comprehensive, storytelling approach to Computing Concepts. The 11th edition has been revamped to include emphasis on mobile computing, cloud computing, privacy/surveillance, and big data.
introduction to information technology : the future now -- the internet & the world wide web : exploring cyberspace -- software : tools for productivity & creativity -- hardware : the CPU & STORAGE - the source of computing power -- Hardware : input & output - taking change of computing & communication -- communication , network & cybertreats : the wired & Wireless world -- personal technology : the future is you -- the ERA of big data : databases, information systems & artificial intelligence -- the challenges of the digital age : society & information technology & language
Includes bibliographical references and index.
Keywords: Computers; Telecommunication systems; Information technology